2018
DOI: 10.1002/jez.2220
|View full text |Cite
|
Sign up to set email alerts
|

Alpha electroencephalographic activity during rapid eye movement sleep in the spider monkey (Ateles geoffroyi): An index of arousal during sleep?

Abstract: There is evidence that some animal species have developed physiological and behavioral mechanisms to monitor potential predatory threats during rapid eye movement sleep (REMS). Nevertheless, it has not been reported in arboreal primates. The present study analyzed the sleeping postures, as well as the electromyographic and electroencephalographic (EEG) activities during three conditions: REMS, non-REMS (N-REMS), and wakefulness in spider monkeys. The study included six monkeys, whose EEGs were recorded at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 89 publications
(135 reference statements)
1
20
0
Order By: Relevance
“…Stoll et al (2016) demonstrated the effects of cognitive control and time on the frontal beta band, while the study by Schmidt et al (2019) showed that beta oscillations are related to sensorimotor function. Thus, a high absolute power in the 18-19 Hz range in the left prefrontal cortex (F3) during N3 sleep suggests that this small portion of the beta EEG band could allow the processing of specific sensory information from the environment, and may be related to specialized brain mechanisms that permit the monitoring of predation risks during sleep, as suggested by Cruz-Aguilar et al, 2018b).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Stoll et al (2016) demonstrated the effects of cognitive control and time on the frontal beta band, while the study by Schmidt et al (2019) showed that beta oscillations are related to sensorimotor function. Thus, a high absolute power in the 18-19 Hz range in the left prefrontal cortex (F3) during N3 sleep suggests that this small portion of the beta EEG band could allow the processing of specific sensory information from the environment, and may be related to specialized brain mechanisms that permit the monitoring of predation risks during sleep, as suggested by Cruz-Aguilar et al, 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…around its body and its legs hugging the tree trunk (Cruz-Aguilar et al, 2018b). To date, however, studies of the neurophysiology of sleep in arboreal primates are scarce.…”
mentioning
confidence: 99%
See 3 more Smart Citations